Ockham's conception of logic as a rational science. An inferentialist interpretation - Vaughan, N (2013)
This thesis is a detailed examination of the logico-semantic system propounded by the English philosopher and theologian William of Ockham (c.1287 – c.1347). It provides a reinterpretation of Ockham's account of mental content and mental-language semantics, as well as of his theory of consequential goodness. It does so from the standpoint of an inferentialist theory of meaning, in rejection of previous attempts made from the standpoint of internalist and externalist theories of mental content. Chapter 1 ('The Scientic Status of Logic') provides an account of Ockham's understanding of logic as a rational, practical, ostensive science. Chapter 2 ('The Received Interpretation') presents and casts doubt upon the arguments put forward by the defenders of both externalist and internalist construals of Ockham's semantic theory. Chapter 3 ('An Inferentialist Construal') presents the central tenets of a inferentialist theory of meaning. In order to show how Ockham's system can be understood within such a semantic paradigm, we will have to set out at least three things. First, Chapter 4 ('Ockham's Propositionalism') argues that the mature Ockham actually embraced a propositionalist theory of meaning. Second, Chapter 5 ('Obligationes and the Normativity of Asserting') seeks to prove that such a theory of meaning can only be properly understood against the normative background provided by his theory of obligationes. Finally, Chapter 6 ('Consequences') argues that Ockham's theory of consequential goodness is materialist, not formalist. That is to say, that the goodness of a certain kind of consequence ultimately depends upon the meaning of its propositional parts, rather than upon its structure. It is then shown that all remaining kinds of consequences (syllogisms included) are to understood with respect to these material inferences. The main sources of this research are Ockham's Ordinatio, his Summa logicae, and his Quodlibeta septem. As regards the inferentialist theory of meaning, Robert Brandom's Making it Explicit (1994) and Wilfrid Sellars 'Inference and Meaning' (1953) were essential to this research.